Preface - Carey, B; Warman, C (Wiley, 2022)
This special issue of the Journal for Eighteenth-Century Studies is the second of two that aim to reflect the range and diversity of research that was presented in July 2019 at the International Congress on the Enlightenment at the University of Edinburgh...